Tackling the Demographic Challenge in Uganda - World Bank (World Bank, Washington, DC, 2020)
At the moment, a child born in Uganda will be only 38 percent as productive when she grows up as she can be if she enjoyed complete education and full health, according to the human capital index (HCI) one of the lowest levels in the world. It will be necessary to ensure that the growing population bulge will be engaged in productive economic activities that are adding value to economy. This report examines what it will take for Uganda to tackle the demographic challenge in the next four decades. The report also explores the effort required to ensure that future generations of Ugandans enjoy higher levels of access to basic services, a necessary condition to fully benefit from a demographic transition. The main objective of the report is to inform policymakers and relevant stakeholders in Uganda as they formulate their plans for the medium term. The report is organized as follows: chapter one gives introduction. Chapter two characterizes Uganda’s progress in terms of its demographic transition, describes its most recent demographic trends, and shows some correlates of the country’s fertility levels. The population projections under the medium and low-fertility variants for the period 2020-2060 are presented in chapter three, while chapter four explores the implications in terms of service delivery of these projections under the business as usual and enhanced equilibrium scenarios. Based on these same projections, chapter five presents the expected trends of select labor market and poverty indicators.